2021
DOI: 10.21203/rs.3.rs-943276/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

QRS Fragmentation in Preserved Ejection Fraction Heart Failure: Functional Insights, Pathological Correlates, and Prognosis

Abstract: Backgrounds: Fragmented QRS (fQRS) morphology as a surrogate marker of the possible presence of myocardial scarring has been shown to confer a higher risk in patients with reduced ejection fraction heart failure. We aimed to investigate the pathophysiological correlates and prognostic implications of fQRS in patients with preserved ejection fraction heart failure (HFpEF). Methods and Results: We consecutively studied 960 patients with HFpEF (76.4±12.7 years, men: 37.2%). fQRS was assessed using a body surfac… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Only lateral fQRS was associated with a higher risk of all‐cause mortality, arrhythmia, and cardiogenic death (Terho et al., 2014). Another study in heart failure patients with preserved ejection fraction showed that both inferior and anterior/lateral fQRS were associated with a higher‐risk cardiovascular and all‐cause mortality (Sung et al., 2023). The prognostic value of fQRS in cancer populations will be the subject of further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Only lateral fQRS was associated with a higher risk of all‐cause mortality, arrhythmia, and cardiogenic death (Terho et al., 2014). Another study in heart failure patients with preserved ejection fraction showed that both inferior and anterior/lateral fQRS were associated with a higher‐risk cardiovascular and all‐cause mortality (Sung et al., 2023). The prognostic value of fQRS in cancer populations will be the subject of further investigation.…”
Section: Discussionmentioning
confidence: 99%